Developing and Deploying an XML-based Learning Content Management System at the FernUniversität Hagen - Gerd Steinkamp; Albert Bullig; Eberhard Heuel; Firoz Kaderali; Heinz Müller; Gunter Schlageter (FernUniversität Hagen, 2005)
This paper is a report about the FuXML project carried out at the FernUniversität Hagen. FuXML is a Learning Content Management System (LCMS) aimed at providing a practical and efficient solution for the issues attributed to authoring, maintenance, production and distribution of online and offline distance learning material. The paper presents the environment for which the system was conceived and describes the technical realisation. We discuss the reasons for specific implementation decisions and also address the integration of the system within the organisational and technical infrastructure of the university.